Exploratory study of media buying behaviours : a non-store retailing comparative study. - Lee, Kheng Nee. (2008)
This research explores in-home buying behaviour across two different mediums, television and the Internet. It examines the behaviour by variables namely, perceived risk, perceived convenience and likelihood of purchase across different demographic and psychographic groups.